Hypoxia: Adaptation Mechanisms and Their Impact on Organs - Rifda El Mahroos; Shellya Puti Sudesty; Rifka Wangiana Yulia Putri (Faculty of Medicine - Universitas Pembangunan Nasional Veteran Jawa Timur, 2026)
Background: Hypoxia is a decrease in tissue oxygen that induces the activation of hypoxia-inducible factor (HIF) and cellular responses such as metabolic changes, angiogenesis, and inflammatory modulation. This initial adaptive response can become maladaptive with prolonged or repeated exposure. Methods: This article is a narrative review that examines literature from 2015–2025 from PubMed, ScienceDirect, and Google Scholar. Searches were conducted using keywords related to